Pilot-Aided Simultaneous Communication and Localisation (PASCAL) Under Practical Imperfections - Shuaishuai Han; Mohammad Al-Jarrah; Emad Alsusa (IEEE Open Journal of the Communications Society)
This paper presents a novel system model, termed Pilot-Aided Simultaneous Communication and Localisation (PASCAL), and evaluates its performance under practical gain and phase imperfections. The system considers multiple single-antenna unmanned aerial vehicles (UAVs) transmitting data packets to a multi-antenna base station (BS), which simultaneously detects communication signals and localises UAVs using pilot symbols embedded in the packets. Two receiver processing approaches are proposed: (1) disjoint localisation and communication using maximum likelihood estimation and (2) joint localisation and data detection via newly developed algorithms. To assess localisation performance under gain-phase imperfections, the average Cramér-Rao lower bound (CRLB) is derived, while the average sum data rate (SDR) for UAV communication is obtained in closed form. The derived expressions are validated through simulations, demonstrating their accuracy. Our results indicate that, while the proposed PASCAL system can be sensitive to gain-phase imperfections, like other state-of-the-art methods, it remains an efficient and robust approach for achieving reliable simultaneous localisation and communication.